Gastric-type endocervical adenocarcinoma: a case report and literature review - Wen, Xiao; Yu, Li; Liu, Xiangyu; He, Xinjia; Zhao, Yuanyuan; Li, Guoliang (Frontiers in Oncology, 2024)
Gastric-type endocervical adenocarcinoma (G-EAC) represents a rare variant of cervical mucinous adenocarcinoma that is typically unrelated to human papillomavirus (HPV) infection. G-EAC exhibits highly atypical clinical presentations and characteristics, and aggressive biological behavior often leads to challenges in timely diagnosis. Here, we present a case study involving a 74-year-old Chinese woman who experienced urinary incontinence for one month. Biopsy pathology confirmed the diagnosis of G-EAC, revealing stage IVa by imaging examinations. The patient subsequently underwent three cycles of chemotherapy, followed by adjuvant radiotherapy and surgical excision of residual tumor foci. This comprehensive treatment approach yielded a favorable survival outcome. For patients with advanced G-EAC, a multimodal therapeutic approach holds promise and warrants further exploration.